Carbonate Chemistry and Isotope Characteristics of Groundwater of Ljubljansko Polje and Ljubljansko Barje Aquifers in Slovenia - Sonja Cerar; Janko Urbanc (The Scientific World Journal)
Ljubljansko polje and Ljubljansko Barje aquifers are the main groundwater resources for the needs of Ljubljana, the capital of Slovenia. Carbonate chemistry and isotope analysis of the groundwater were performed to acquire new hydrogeological data, which should serve as a base for improvement of hydrogeological conceptual models of both aquifers. A total of 138 groundwater samples were collected at 69 sampling locations from both aquifers. Major carbonate ions and the stable isotope of oxygen were used to identify differences in the recharging areas of aquifers. Four groups of groundwater were identified: (1) Ljubljansko polje aquifer, with higher Ca2+ values, as limestone predominates in its recharge area, (2) northern part of Ljubljansko Barje aquifer, with prevailing dolomite in its recharge area, (3) central part of Ljubljansko Barje aquifer, which lies below surface cover of impermeable clay and is poor in carbonate, and (4) Brest and Iški vršaj aquifer in the southern part of Ljubljansko Barje with higher Mg2+ in groundwater and dolomite prevailing in its recharge area. The radioactive isotope tritium was also used to estimate the age of groundwater. Sampled groundwater is recent with tritium activity between 4 and 8 TU and residence time of up to 10 years.